What a Map and a Portrait Have in Common. Issue 3 (3rd July 2021) - Hanson, Marta
Abstract: This short essay summarizes thoughts inspired by two images chosen for covers of the journal EASTS—a portrait of an East Asian female scientist and a map of the Pacific Ocean region centered on Taiwan. At first glance, they appear to bear no relation to each other until one realizes that they were both produced in 1944 within the Japanese "Greater East Asia Co-prosperity Sphere"—the map in colonial Taiwan and the portrait in colonial Korea.